Critical Thinking in Virtual Learning Environments: Validation of a Career Choice E-Case - Antonio Cañongo, Anayanzin (Consorcio de Universidades Mexicanas A.C., 2023)
The aim of the study was to design and validate electronic case studies (e-case) to explore and enhance critical thinking skills. This research employed Design-Based Research (DBR) composed of two stages: 1) Design and validation of an e-case; 2) Validate a website. Seven expert judges participated in each stage. Content Validity Index (CVI) and percentage of agreement among expert judges of the evaluated dimensions of the e-case and website were obtained. The findings of the research reveal that the e-case was interesting and motivating for students, and consists of materials and activities suitable for the target population. In conclusion, the e-case was a relevant and alternative pedagogical device to explore and encourage critical thinking skills related to career choice in virtual learning environments.